Ultrasound-guided acupuncture therapy in Korea: advancing traditional practices with new technology - Lee, Sang-ho; Youn, You Suk; Kim, Min Chul; Sun, Junghum; Ha, Donghyon; Kim, Tae-Hun (Frontiers in Medicine, 2025)
Ultrasound-guided acupuncture is a novel technique that utilizes ultrasonography to visualize needle placement in real-time, enhancing precision and reducing adverse events. In South Korea, the dual medical system has led to disputes over Korean Medicine doctors’ use of biomedical devices. However, in 2022, the Supreme Court ruled that Korean Medicine doctors’ use of ultrasound devices is not illegal, enabling broader clinical application. Ultrasound-guided acupuncture involves inserting a needle to a precise depth to reach targeted tissue while applying manual techniques based on ultrasound-guided injection therapy principles. This technique requires ultrasonography with a linear probe and is commonly used to treat musculoskeletal conditions, such as shoulder pain. By improving accuracy, ultrasound-guided acupuncture enhances the effectiveness and safety of both traditional acupuncture and emerging techniques like acupotomy and pharmacopuncture. However, its clinical use remains limited due to the lack of national health insurance coverage and insufficient clinical evidence. To establish its efficacy and safety, comparative clinical trials should first focus on musculoskeletal disorders, pain management, and neurological conditions, which are among its most frequent applications in Korea.